Study on Distilation Process of Patchouli Oil Through Leaves Delignification - Nasruddin .; Gatot Priyanto; Basuni Hamzah (Jurnal Teknologi dan Industri Pangan, 2005)
Research was objected to determine the effect of patchouli leaves preparation on the distillation efficiency and quality of patchouli oil. The patchouli leaves (Pogostemon cablin Benth) were taken from Pandan Dulang Village, Muara Enim. It was separated from the stems and dried until maximum moisture content of 15%. Experiment was conducted in two replications base on these treatments, i.e delignification temperature (550C, 800C) and fermentation time (2, 4, 6, 8, days). NaOH solution (0,25%) was used for delignification. The distillation process was conducted at 100  20C and ambient pressure environment. Patchouli oil quality was expressed as several parameter such as ester numbers, acid numbers, and specific gravity. The result showed that increasing of fermentation time is followed by decreasing of the patchouli oil quality. Delignification at 550C for 6 days was identified as the treatment produced the highest efficiency process which about 2,346% (w/w) of patchouli oil that could be extracted and showed specific gravity 0.959, acid number 0,761 and ester number 4,561. All patchouli oil produced using the treatment of fermentation time were in the range of physico-chemical quality standard of patchouli oil given by SNI no 06-2385-1991. Keyword : patchouli leaves, preparation, delignification, fermentation, and distillation